Forensic dental biometry - a human identification system using panoramic dental radiographs based on shape of mandibular bone. (2018) - Banday, Mahroosh; Mir, Ajaz Hussain
Dental biometrics is a new and growing area of forensic biometrics that uses the unique features of dental structures from dental radiographs to automatically establish a person's identity from their dental remains when the conventional biometric features are not available. In this paper, we present a new and efficient approach for identifying people, by using the structure of mandible from the panoramic dental radiographs as a biometric identifier. The system automatically segments the mandible from dental panoramic images to extract the representative feature vectors for each mandible, which are later used for matching and identification. The experimental results of the proposed system using a database of 120 ante-mortem and 90 post-mortem panoramic dental images show that the system is robust and effective in identifying individuals and exhibits a high recognition rate (RR) up to 98.79%, low equal error rate (EER) of 1.5% and a remarkable identification performance.